أثر ملتقيات الاستثمار السياحي على تنمية السياحة والناتج المحلي الإجمالي في سورية - عكروش محمد; شيخ حسين صطوف; محسن زهيري علاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن إدراك الحكومة السورية لأهمية القطاع السياحي, لما يتميز به من مقومات طبيعية وتراثية, جعل سورية في مقدمة دول المنطقة التي يستحوذ فيها هذا القطاع على اهتمام كبير, من خلال التعريف بمزاياه وخصائصه, حيث سعت الجهات الحكومية ذات الصلة إلى خلق صيغ جديدة للترويج السياحي والكفيلة بتدعيم الاستثمار في المشروعات السياحية, ومن أهم هذه الصيغ ملتقيات الاستثمار السياحي التي بدأت بشكل دوري ومنتظم منذ العام (2005) وأسهمت إلى حد فاعل في التعريف بالبيئة المناسبة والبنية التحتية المناسبة للسياحة السورية وبالمنتج السياحي السوري الغني والمتنوع, وهذا ما كان له أثر إيجابي مباشر في الاقتراب من تحقيق التوازن بين العرض والطلب السياحي ورفد خزينة الدولة، وزيادة فرص العمل المتاحة، ونمو حصة القطاع السياحي في الناتج المحلي الإجمالي. وبالتالي فإن هذا الاهتمام الحكومي واسع النطاق بالترويج والاستثمار السياحي في ظل الوعي بضرورة تنويع وإغناء المنتجات السياحية, أسهم من جهة في إغناء العرض السياحي وأدى من جهة أخرى إلى تخفيف سمة الموسمية عن السياحة السورية. The realization of the Syrian Government of the tourism sector makes of Syria a developed country in the region due to the natural and heritage factors in addition to the interest in this sector. Syria has defined its merits and characteristics. The concerned governmental bodies have initiated to create new models in promotion and support of investment in tourist projects. Most important of those models has started periodically and regularly since 2005. The Syrian concerned bodies have participated a great deal in introducing the suitable environment and infrastructure in tourism in Syria and the GDP in Syrian tourism which is very rich and variable .This has had a direct positive impact in reaching the balance between the demand and the offer in tourism. This will certainly tribute the treasury of the Syrian State with new funds and shall definitely increase creation of job vacancies .Moreover, the portion of the tourism will grow in the DGP. Consequently, the wide-band governmental interest in promotion and investment of tourism comes from the realization of the importance of enriching the tourist products. In turn, this has enriched the tourist offering and decreased the aspect of seasonal Syrian tourism.